REPRESENTATION OF MAN IN MAGAHI FOLK TALES: A STUDY OF MALE STEREOTYPING IN ‘CHHATRI GHUGHULIA’ - Anand, Rituraj; Sehrawat, Anil; Singh, Bijender (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Folk Tales are oral narratives that carry the social and cultural treasure of a society, and help in entertainment, learning and the preservation of cultural values and beliefs. Compared to studies done on women in the Magahi Folk Tales, there is a dearth of research on men in these folk tales. By critically engaging in studying the different attributes given to men in the Magahi folk tales and how the stereotyping leads to societal expectations, we understand the socio-cultural framework of masculinity in the Magahi society. The Gender traits given by John J. Macionis in his book Sociology, help us to analyse the Magahi folk tale- Chhatri Ghughulia in Sheela Verma’s book- Magahi Folklore and Folk Tales. The recurring themes of these narratives in Magahi society and the words used in the tales to describe the characters and their actions, make us understand how the masculine identity is formed in the Magahi Society. This research paper is an attempt to broaden the horizon of studies done on Magahi Folk Tales and put forward an analysis of a Magahi Folk Tales from the perspective of Masculinity Studies. This study can be significant in understanding the complexity of gender identity and contribute in the new discourses on masculinity in the present times.